Association between thrombocytopenia and delirium tremens in alcohol withdrawal syndrome in tertiary care centre - Mahat, Pradeep; Aacharya, Ramesh Prasad; Bajracharya, Manjita; Shrestha, Susmita; Mishra, Abhisek; Neupane, Jeevan; KC, Bipana; Thapa, Rikhi Raj; Gautam, Sundar; Bhandari, Jeetendra (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Delirium Tremens (DT) is a severe spectrum of Alcohol Withdrawal Syndrome (AWS), which could potentially result in death unless managed promptly and adequately. It has been shown in various studies that alcohol withdrawal is associated with the thrombocytopenia. Almost the studies are from outside the country and limited study are from inside the country. This study aims to explore the association of DT and AWS in terms of platelets count. Method: This was an analytical cross-sectional study design. This was conducted from December 2022 to December 2023 after the research proposal was approved by the Institutional Review Committee. For this study patients who presented to the Emergency Department with alcohol withdrawal symptoms were enrolled through a non-probability purposive sampling method. Result: Of the 227 patients enrolled in the study, 16 (7.04%) developed delirium tremens, with all DT cases associated with thrombocytopenia. Thrombocytopenia was present in 183 (80.62%) of the total patients. Notably, 16 (8.7%) of patients with thrombocytopenia experienced the cooccurrence of both DT and thrombocytopenia. The study demonstrated a statistically significant relationship between thrombocytopenia and DT (p=0.042). These findings suggest an association between thrombocytopenia and the development of DT, emphasizing the potential clinical importance of considering thrombocytopenia in the context of DT occurrence. Conclusion: The study establishes a statistically significant association between thrombocytopenia and Delirium Tremens, as all patients who developed DT had thrombocytopenia.